Moralism : a study of a vice - Taylor, Craig, 1963- (Montreal [Quebec] : McGill-Queen's University Press, 2012)
"In Moralism: A Study of a Vice, Craig Taylor delves into one of the most overlooked ethical concerns of our time: the vice of moralism, or the distortion of moral thought, reflection, and judgment. This flawed tendency in human nature is pervasive on all levels of society, and affects people from all walks of life - from the philosopher to the pundits and politicians. Covering a wide variety of topics, Moralism takes on such salient issues as the nearly impossible demands of stringent morality, the conflict between morals and other values, and the contrast between the practice of moral philosophy and other modes of moral thought and reflection. In connecting his argument to the world at large, Taylor draws upon examples of moralism in the media, in literature, and in art. This highly original and provocative study will be of interest to students of philosophy, psychology, theology, and media, and to anyone who takes an interest in contemporary morality."--Publisher's website.
Preface -- Moralism and related vices -- "The Scarlet Letter": "a tale of human frailty and sorrow" -- Trusting oneself -- Overweening morality -- Moral judgement and moral reflection -- Moral difference -- Public moralism -- Conclusion.
Includes bibliographical references (pages163-183) and index.
Keywords: Ethics; Judgment (Ethics); Morale; Jugement (Morale); PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- Social; PHILOSOPHY -- General; Ethics; Judgment (Ethics); Electronic books